Management and administration of distance learning programmes in Nigeria (2011)
"The challenges of ever-increasing demand for university education in the face of inadequate human and infrastructural resources and rapidly increasing population have necessitated distance learning programmes. This study evaluated Universities of Ibadan and adminstration of universities of Ibadan and Lagos distance learning programmes. Samples of 560 participants (400 distance learning students,80 academic and 80 non-academic staff of the programmes) were proportionally selected. One research question guided the research. Three validated instruments were used to collect data. Data were analysed using independent t-test. ULDLI was significantly better than UIDLC from the perspectives of studetns: (t=7.51, df=398,P<0.05) and teaching staff: {t=-5.69,df=78,P<0.05] while non-teaching staff of both institutions revealed that there was no significant difference in the quality of administration. The two institutions must aim at improving teaching-learning reseources, staff capacity development, learner support services, and increase the number of courses available to prospective candidates in order to position distance education in Nigeria for global competitiveness."